2021
DOI: 10.7554/elife.65810
|View full text |Cite
|
Sign up to set email alerts
|

Transient kinetic studies of the antiviral Drosophila Dicer-2 reveal roles of ATP in self–nonself discrimination

Abstract: Some RIG-I-like receptors discriminate viral and cellular dsRNA by their termini, and Drosophila melanogaster Dicer-2 (dmDcr-2) differentially processes dsRNA with blunt or 2 nucleotide 3'-overhanging termini. We investigated the transient kinetic mechanism of the dmDcr-2 reaction using a rapid reaction stopped-flow technique and time-resolved fluorescence spectroscopy. Indeed, we found that ATP binding to dmDcr-2's helicase domain impacts association and dissociation kinetics of dsRNA in a termini-dependent m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 60 publications
5
26
0
Order By: Relevance
“…There are extensive studies on the 5′-triphosphate recognition by the C-terminal domain of RIG-I that has similar conformational change of helicase after dsRNA binding 28 , 29 . Dcr-2 may sense the 5′-triphosphate of RNAs using a similar binding pocket to that demonstrated previously 12 , 27 . Recent single-molecule analysis 19 supports the conclusion from our structures in this study that terminal loading of dsRNA as the initial step and translocation along the dsRNA are required to activate the processive cleavage activity of Dcr-2.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…There are extensive studies on the 5′-triphosphate recognition by the C-terminal domain of RIG-I that has similar conformational change of helicase after dsRNA binding 28 , 29 . Dcr-2 may sense the 5′-triphosphate of RNAs using a similar binding pocket to that demonstrated previously 12 , 27 . Recent single-molecule analysis 19 supports the conclusion from our structures in this study that terminal loading of dsRNA as the initial step and translocation along the dsRNA are required to activate the processive cleavage activity of Dcr-2.…”
Section: Discussionmentioning
confidence: 52%
“…Recent research suggested that ATP is required for recognition and discrimination of dsRNA termini 12 , 27 . We have identified a 5′-phosphate-binding pocket in Hel2i in the initial binding state (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The defining structural difference between Class II and Class III proteins is the addition of an N-terminal duplex RNA-activated ATPase (DRA) helicase domain, also sometimes referred to as a DExD/H-box helicase domain. The DRA helicase domain, formed by three subdomains, Hel1, Hel2i, and Hel2, binds and unwinds the hairpin loop region of the pre-miRNA substrate. , As shown in Figure , while the majority of Dicer and Dicer-like enzymes contain an N-terminal DRA helicase domain, there is variability between species regarding whether this domain is ATP dependent or independent. These differences in ATP dependence are seemingly linked to Dicer’s substrate specificity during cleavage. , For instance, in Drosophila , Dicer-1 is ATP independent and primarily cleaves pre-miRNA, while Dicer-2 requires ATP to cleave pre-small interfering RNAs (siRNA). , Interestingly, the minimal Giardia Dicer lacks the helicase domain altogether despite being classified as a Class III RNase III enzyme . Lack of a helicase domain may suggest an evolutionary shift in Dicer enzymes requiring a more sophisticated means to differentiate RNA substrates in higher eukaryotes.…”
Section: Structural Diversity Among Rnase III Family Enzymesmentioning
confidence: 99%
“…Unlike humans which only contain one copy of Dicer, Drosophila has evolved two copies of Dicer known as Dicer-1 and Dicer-2. , As previously mentioned, these Dicer proteins differ in their ATP dependence with dmDicer-1 cleaving pre-miR substrates independent of ATP, while dmDicer-2 depends on ATP to cleave long dsRNA and discriminate between the dsRNA termini for specific cleavage. ,,, This functional duality is dependent on dmDicer’s helicase domain, but until very recently, we lacked structural insights to explain these activity differences. Using cryo-EM, multiple structures of dmDicer-1 and dmDicer-2 , in a variety of conformational states have been determined ranging in resolution from 5 to 3 Å.…”
Section: Cryo-em Studies Of Drosophila Dicer-1 and Dicer-2 Reveal Ste...mentioning
confidence: 99%
See 1 more Smart Citation